The truth about psychics [large type] - Browne, Sylvia (Thorndike Press large print basic, 2010)
Traces the history of spirituality and explains how to know if a psychic is real and is telling the truth. Explors topics such as telling the future, astral projections, and contacting residents of the spiritual world.